Ensino de ciências: um estudo sobre o currículo em uma escola ribeirinha do Miriti em, Parintins, AM - Souza, Silvia Pantoja de (2021)
SCIENCE TEACHING: A STUDY OF THE CURRICULUM IN A RIVERSIDE MIRITI SCHOOL, IN PARINTINS, AM This research aims to understand the constitution of the educational practice in Science Teaching, in the construction of the Curriculum, in a Miriti riverside school in Parintins, AM. Methodologically, it presents a qualitative approach and a dialectical perspective. The study was conducted in a Miriti riverside school, in the Vila Amazônia Settlement, in Parintins, Amazonas. Data collection occurred through semi-structured interviews and the study of the school's Political Pedagogical Project. The subjects were eight people, namely: a 5th grade science teacher; the school manager/coordinator, and six community members. The theoretical and methodological framework was based on the studies of Sacristán (2000), Bourdieu (2004), Silva (2010), Lopes and Macedo (2011), Moreira and Silva (2013); Freire (2019 a), (2019 b); Arroyo (2013) and Goodson (2018) for the discussion on Curriculum. The reflections about Science Teaching were grounded by Chassot (2008) and (2010); Krasilchik (2000); Delizoicov (2009) and Oliveira (2016). While the writings of Souza (2013), Bruce and Costa (2019), Vasconcelos (2017) and Caldart (2009) grounded the understandings about riverine contexts and Field Education. Inthediscussion ofthedata, wesystematized the information collected, throughtriangulation and the analysis of the results was from the reading in a dialectical perspective. We present as a result, a research carried out in a riverside territory, with a cultural diversity linked to the Environment and to popular social movements. In the conceptions about curriculum issues, there is a divergence that highlights a curriculum that is closed to school contents, while at the same time it highlights the need to understand it as a means of formation, an idea that is close to the proposal of this study. Regarding Science Teaching, the dialogues converge with the compressions that highlight it as a field linked to nature studies. The constitution of teaching happens through contradictions, tensions, and disputes in the midst of the struggle for the defense of a school construction favorable to the community practices of the subjects. In this reality, there are factors that hinder a school construction focused on local particularities, such as: the paralization of environmental projects, school management, the need for involvement in social community issues, the lack of physical structure and teaching resources, as well as thedistance betweentheschool andthecommunity. These issues translate intolimits,thechallenges consisted in the union between the school and the community, the inclusion of cultural aspects in the school contents, and the resumption of socio-cultural projects. Conversely, the possibilities are contextualized teaching, the historical and cultural knowledge built in the community, and the work practice articulated to the sovereignty of the waters and the forests. In this field of riches, the subjects are active in their social issues and among the community agreements and disagreements, which are present in the construction of teaching to collaborate with a school reality focused on the experience in the community. Therefore, the considerations constructed here point to the understanding of the logic of reproduction, through reflections on the process of construction of the educational path. Thus, we understand that the curriculum construction covers the sociocultural issues for the formation of a society. In this sense, an educational construction, from Science Teaching, in riverside schools, can occur in an open and problematizing path, in view of a social formation, which prepares students for the exercise of citizenship, in accordance with their living spaces, or not, this will depend on the conditions given for this understanding. For this purpose, we emphasize that the Political Pedagogical Project, in these schools, canbeaspacefor constant construction, reflection,anddialoguebetweenthecommunityand theschool, aimingattheorganization ofaneducationalpracticethatfavors thedevelopmentof students intheir place of life. Wealsohighlight theneedfor Continuing Education for teachers,in order to provide them with the conditions to act in this universe, with challenges and possibilities. Keywords: Curriculum. Science Teaching. Contextualization.